Case report Klippel-Trenaunay Syndrome coexisting with others vascular abnormalities - Uchańska, Grażyna; Wankiewicz, Anna; Romańska-Gocka, Krystyna; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Klippel-Trenaunay syndrome (KTS) is a rare congenital malformation characterized by the triad of macular vascular naevus, soft tissue and/or skeletal hypertrophy and venous varicosities. Despite of mentioned features KTS has a highly variable clinical presentation. We present the case of the 75 year old woman with KTS diagnosed in elderly, referred to our Clinic because of severe pain and ulceration on limb affected by vascular naevus. We would like to underline the rarity of unilateral localization of naevus on the whole body including face and scalp. Moreover our patient have had rarely described varicosities of upper limb. We We also observed hepato and splenomegaly, bone abnormalities and the coexistance of some features characteristic for others vascular malformations such as Kassabach-Metritt syndrome (trombocytopeny and hypofibrinogenemy) and Parkes-Weber syndrome (arterio-venous shunting, heart insufficiency). We present this KTS in the association with review of the literature on the classification of vascular abnormalities, etiopathogenesis and variety of clinical manifestation.